2007
DOI: 10.1111/j.1600-0501.2007.01436.x
|View full text |Cite|
|
Sign up to set email alerts
|

What dentition assures oral function?

Abstract: The World Health Organization goal for the year 2000, namely to maintain a natural dentition of not less than 20 teeth throughout life, is substantiated by the current literature review as this proposed dentition will assure an acceptable level of oral function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
207
0
11

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(224 citation statements)
references
References 105 publications
(144 reference statements)
6
207
0
11
Order By: Relevance
“…The number of teeth, and number of occluding pairs of teeth required for satisfactory social and biological function, has received considerable attention over the past two decades [29][30][31][32] with the consensus that 20 teeth (10 occluding pairs of teeth) provide adequate oral function. Thirty-nine per cent of CHAMP men had 21 or more natural teeth, and just over 65% relied on prosthetic teeth to provide satisfactory occlusion (≥10 FTU).…”
Section: Fac Wright Et Almentioning
confidence: 99%
“…The number of teeth, and number of occluding pairs of teeth required for satisfactory social and biological function, has received considerable attention over the past two decades [29][30][31][32] with the consensus that 20 teeth (10 occluding pairs of teeth) provide adequate oral function. Thirty-nine per cent of CHAMP men had 21 or more natural teeth, and just over 65% relied on prosthetic teeth to provide satisfactory occlusion (≥10 FTU).…”
Section: Fac Wright Et Almentioning
confidence: 99%
“…Indeed, having fewer than 20 teeth was found to be associated with poorer chewing ability and lower consumption of more valuable and healthy foods [6,7]. It was found that not only the number of teeth is important but also their distribution in the oral cavity [8]. The UK National Diet and Nutrition Survey demonstrated an association between the number of posterior contacts and freedom of food choice, which affected individual's nutrients intake.…”
mentioning
confidence: 99%
“…5(12), 88-100 89 of the molar teeth 16 . Contrary, several studies and reviews have indicated that twenty occluding teeth provide sufficient oral functional ability and the need to replace all missing posterior teeth has been questioned 1,7,11,14,[16][17][18][19][20] When dentists extend or reconstitute reduced, shortened or discontinuous dental arches and replace missing teeth in either anterior or posterior regions to create a complete dental arch (CDA), the following interventions are usually recommended: removable partial denture prosthesis (RPDP) or cantilever fixed denture prosthesis (CFDP), including resin-bonded bridges and implant-retained fixed partial dentures (IFPDs) 18,21,22 .…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%